AUGMENTED REALITY FOR UNIVERSITAS ISLAM NEGERI WALISONGO'S PROFILE USING AGILE METHODOLOGY - Siti Nur’aini; Muhammad Naufal Muhadzib Al-Faruq (Informatika, Universitas Jenderal Soedirman, 2022)
The use of Information Technology for the process of delivering information has grown so rapidly. One of them is Augmented Reality. Augmented Reality is widely implemented for various things, including in the world of education, health, military, entertainment and many others. Augmented Reality is a technology that combines virtual objects and the real world in real-time and interactively. This research developed an Augmented Reality Application that can be used to introduce Universitas Islam Negeri (UIN) Walisongo more broadly, attractively, interactively, and competitively. This application is named AR UINWS. Agile methodology was chosen to develop AR UINWS. The results show that the agile methodology is suitable to be implemented because of its flexibility, so that the needs of developing applications can be easily adapted. AR UINWS works well on all types of android devices that have a minimum camera resolution of 720x1280 pixels. AR UINWS can detect markers if the marker surface is visible at least 65% of the total marker surface area. This application can detect markers of various sizes as long as the background is light. The size of the marker that can be detected is 1.5x2 cm with the minimum distance between the marker and the android device is 1 5cm. While the largest marker size being tested is 15x23cm with the minimum distance between the marker and the android device is 150 cm.